ダイ4ジ ナンキョク チイキ カンソクタイ エットウタイ ノ チョウサ リョコウ ニオケル キショウ カンソク ニツイテ - 吉田, 栄夫; ヨシダ, ヨシオ; 村越, 望; ムラコシ, ノゾミ; 矢田, 明; ヤタ, アキラ; YOSHIDA, Yoshio; MURAKOSHI, Nozomi; YATA, Akira (国立極地研究所, 1962)
P(論文) Climatological observations were made by the field party of the wintering party of JARE IV in survey trips en route, in 1960. The trips in which the surface observations were carried out are as follows (Names parenthesized are observers.): April 15-May 9: The first Shirase Glacier reconnaissance survey trip (Y. YOSHIDA), May 17-May 25: The Honnorbrygga Glacier survey trip (Y. YOSHIDA), Aug. 16-Aug. 23: The sea ice survey trip (Y. YOSHIDA), Sept. 12-Sept. 29: The reconnaissance traverse to inland (Y. MURAISHI), Sept. 23-Sept. 29: The second Shirase Glacier survey trip (N. MURAKOSHI), Nov. 1-Dec. 15: The Yamato Mountains traverse (Y. YOSHIDA). The data obtained and some comments on climatic conditions around Lutzow-Holm Bay are given here. The surface observations including air temperature, atmospheric pressure, wind velocity, wind direction, cloudiness and weather were made ordinarily twice a day, and remarkable meteorological phenomena were recorded. On the basis of these results the following are concluded tentatively: i) The inland in the distance of 200km south of Syowa Base seems to be often involved in cyclonic circulations. At the end of November a snowfall supposedly caused by a cyclone which passed over the edge of a pack ice region off Lutzow-Holm Bay was observed in the Yamato Mountains 300 km south of the Base. This is deduced from the weather condition and the changes of the atmospheric pressure (Fig. 4) compared with Syowa Base at the same period. ii) Climatic conditions, especially the wind direction and velocity, are greatly controlled by the landforms of the regions. On the sea ice in the vicinity of the east coast of Lutzow-Holm Bay, the wind velocity decreases in proportion to increase in the distance from the coast, whereas snow depth becomes greater. The greater snow depth off the coast is implied by a number of icebergs with round tops, found at the center of Lutzow-Holm Bay. They are found in succession on the extension line of the Shirase Glacier. They have the shape of a gentle ...